Arabis erecta (Brassicaceae), a new species from Republic of Korea - Kim, Yoon-Young; Jang, Changgee; Ji, Seong-Jin; Oh, Sang Heon; Na, Nu-Ree; Leem, Hyosun; Kim, Tae-Weon; Lee, Woo-Rak; Lim, Yong Pyo (Phytotaxa, 2016)
A new species of Arabis L. (Brassicaceae), A. erecta Y.Y. Kim & C.G. Jang, was discovered in Gyeongsangbuk-do Province, Republic of Korea and is described and illustrated here. The species is similar to A. stelleri DC. and A. takesimana Nakai in its general vegetative and floral morphology. However, the new species is distinguished by its glabrous leaves surface, not inflated receptacle, and fruiting pedicels and siliques appressed to the rachis. In addition, the diagnostic characters between related species, an identification key, and a distribution map are provided.